The effect of fixed orthodontic treatment with Edgewise and Straightwire techniques on white spot lesions incidence and accumulation of Streptococcus mutans bacteria - Elfira Maharani; Dyah Karunia; Pinandi Sri Pudyani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: Fixed orthodontic appliances, such as Edgewise and Straightwire techniques, can increase the amount of plaque retention containing Streptococcus mutans (S. mutans), which can lead to white spot lesions. Purpose: The aim of this study is to analyse the correlation of fixed orthodontic treatment with Edgewise and Straightwire techniques on the incidence of white spot lesions and accumulation of S. mutans. Methods: The samples consisted of three groups: control group (n=8), Edgewise technique group, and Straightwire technique group. We observed the samples at the sixth month and eighth month of the treatment, after the installation of the fixed orthodontic appliances. The observation of white spot lesions with caries detector was applied in all regions. Bacterial swabs were acquired in the lateral incisor region, then a bacterial culture procedure was carried out on selective media of S. mutans, and then a bacterial count was performed. The data was analysed using two-way ANOVA, the post-hoc least square differences test, and the Pearson’s correlation test. Results: The number of white spot lesions in the Edgewise group was higher than in the Straightwire group in the sixth and eighth month of treatment with insignificant difference (p>0.05). The number of S. mutans bacteria increased in all groups, but there were no significant differences (p>0.05). There was no significant relationship between the number of white spot lesions with the accumulation of S. mutans between groups (p>0.05). Conclusion: The Edgewise and Straightwire techniques increase the incidence of white spot lesions but accumulation of S. mutans with the incidence of white spot lesions has no relationship.